Cross-Skill Redistribution and the Tradeoff between Unemployment Benefits and Employment Protection - Tito Boeri; Jose Ignacio Conde-Ruiz; Vincenzo Galasso (Institute for the Study of Labor (IZA), 2004)
We document the presence of a trade-off between unemployment benefits (UB) and employment protection legislation (EPL) in the provision of insurance against labor market risk. Different countries' locations along this trade-off represent stable, hard to modify, politico-economic equilibria. We develop a model in which voters are required to cast a ballot over the strictness of EPL, the generosity of UBs and the amount of redistribution involved by the financing of unemployment insurance. Agents are heterogeneous along two dimensions: employment status – insiders and outsiders – and skills – low and high. Unlike previous work on EPL, we model employment protection as an institution redistributing among insiders, notably in favour of the low-skill workers. A key implication of the model is that configurations with strict EPL and low UB should emerge in presence of compressed wage structures. Micro data on wage premia on educational attainments and on the strictness of EPL are in line with our results. We also find empirical support to the substantive assumptions of the model on the effects of EPL.
Keywords: J65; J68; D72; 330; employment protection; unemployment insurance; political equilibria; Arbeitslosenversicherung; Kündigungsschutz; Arbeitsrecht; Insider-Outsider-Modell; Vergleich; OECD-Staaten